2013
DOI: 10.1007/s00335-013-9459-x
|View full text |Cite
|
Sign up to set email alerts
|

A coding variant in SR-BI (I179N) significantly increases atherosclerosis in mice

Abstract: Human coding variants in scavenger receptor class B member 1 (SR-BI; gene name SCARB1) have recently been identified as being associated with plasma levels of HDL cholesterol. However, a link between coding variants and atherosclerosis has not yet been established. In this study we set out to examine the impact of a SR-BI coding variant in vivo. A mouse model with a coding variant in SR-BI (I179N), identified through a mutagenesis screen, was crossed with Ldlr (-/-) mice, and these mice were maintained on a We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…17,18,22 Studies in atherosclerosis-susceptible mice showed that inactivating SR-B1 globally or in a liver-specific manner increased atherosclerosis, whereas overexpressing SR-B1 in liver protected against atherosclerosis. 19,[23][24][25][26][27][28][29][30][31][32] These and other studies in mice [33][34][35] suggest a mechanism whereby SR-B1, by mediating hepatic selective HDL-C clearance from plasma, drives atheroprotective reverse cholesterol transport (RCT). Disrupting SR-B1 activity thus blocks hepatic HDL-selective uptake and backs up hepatic RCT, triggering an increase in HDL-C and impairs HDL-dependent cholesterol removal from atherosclerotic plaques.…”
mentioning
confidence: 83%
“…17,18,22 Studies in atherosclerosis-susceptible mice showed that inactivating SR-B1 globally or in a liver-specific manner increased atherosclerosis, whereas overexpressing SR-B1 in liver protected against atherosclerosis. 19,[23][24][25][26][27][28][29][30][31][32] These and other studies in mice [33][34][35] suggest a mechanism whereby SR-B1, by mediating hepatic selective HDL-C clearance from plasma, drives atheroprotective reverse cholesterol transport (RCT). Disrupting SR-B1 activity thus blocks hepatic HDL-selective uptake and backs up hepatic RCT, triggering an increase in HDL-C and impairs HDL-dependent cholesterol removal from atherosclerotic plaques.…”
mentioning
confidence: 83%
“…Regarding the role of SR-B1 in CVD, it has been shown to protect from diet-induced atherosclerosis in apoE-/-mouse models [9,10] while SR-B1 deficient mice with high HDL-C, was associated with increased atherosclerosis and increased expression of inflammatory markers [7]. In line, it has also been shown that a coding variant for SR-B1 (I179N) caused increased atherosclerosis in LDL-receptor knockout mice on a Western-type diet [11]. In humans, variation at the SCARB1 locus (the gene encoding for SR-B1) has been associated to CVD, albeit in a gender specific way [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Then, two novel missense mutations, S112F and T175A, in human SR-BI were identified in patients with atherosclerosis, which led to elevated HDL cholesterol levels[ 27 ]. A coding variant in SR-BI (I179N) significantly increased atherosclerosis, although the mutation did not dramatically affect the plasma lipid levels[ 34 ]. The hydrophobicity of N-terminal half of the extracellular domain of SR-BI was proven to be critical for the SR-BI-mediated cholesterol transport function, and this domain might function by interacting with other integral membrane proteins[ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%